Analysis, evaluation and justification of labor productivity growth in construction - Oleynik, Pavel; Kazaryan, Ruben; Doroshin, Ivan; Avetisyan, Robert (Edelweiss Applied Science and Technology, 2025)
Nowadays, the construction industry demonstrates high positive dynamics. However, its development is constrained by a number of factors, the most persistent being the lack of labor productivity growth in the construction sector. To determine the current value of productivity, the factors influencing it, and to find ways to increase it, methods were used to determine its value, taking into account the influence of one or more factors over the base period, as well as probabilistic models to determine its value in the future after the base period. As a result of the conducted research, it was possible to establish that such labor productivity values are a consequence of the fact that construction organizations do not implement measures to improve organizational and technological solutions aimed at modernizing construction production, as well as the emergence of additional problems in construction production at the present stage. The research shows that active growth of labor productivity indicators is achieved by taking into account large-scale state support by implementing a set of current and strategic measures. Grouped current measures represent an evolutionary path of labor productivity growth, while strategic measures reflect a fundamentally new approach to the development of the entire construction production system.